2012
DOI: 10.1186/1476-511x-11-99
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration in elderly obese patients correlated negatively with intake fatty

Abstract: Study objectivesThe purpose of the present study was to evaluate the relationship between sleep duration and dietary habits in elderly obese patients treated at an institute of cardiology.MethodsThe fifty-eight volunteers were elderly patients with obesity (classified as obese according to BMI) of both genders, between 60 and 80 years of age. All participants were subjected to assessments of food intake, anthropometry, level of physical activity, and duration of sleep.ResultsThe men had significantly greater w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
0
26
1
Order By: Relevance
“…Therefore, study results have been inconsistent. Some studies show sleep quality was improved (Irmisch, Schläfke, Gierow, Herpertz, & Richter, 2007; Santana et al, 2012) when individuals consumed a high fat diet, whereas another study indicated no relationship (Landström et al, 2000). For example, in a study of the impact of fatty acids on sleep in 118 hospitalized male and female participants diagnosed with depression, significant negative correlations resulted among sleep disturbances and fatty acid intakes (Irmisch et al, 2007).…”
Section: Fat Intake and Sleepmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, study results have been inconsistent. Some studies show sleep quality was improved (Irmisch, Schläfke, Gierow, Herpertz, & Richter, 2007; Santana et al, 2012) when individuals consumed a high fat diet, whereas another study indicated no relationship (Landström et al, 2000). For example, in a study of the impact of fatty acids on sleep in 118 hospitalized male and female participants diagnosed with depression, significant negative correlations resulted among sleep disturbances and fatty acid intakes (Irmisch et al, 2007).…”
Section: Fat Intake and Sleepmentioning
confidence: 99%
“…For example, in a study of the impact of fatty acids on sleep in 118 hospitalized male and female participants diagnosed with depression, significant negative correlations resulted among sleep disturbances and fatty acid intakes (Irmisch et al, 2007). Santana et al (2012) studied 58 obese elderly patients (60–80 years of age) of both genders and found that a preference for high energy, dense foods resulted in shorter sleep duration (Santana et al, 2012). …”
Section: Fat Intake and Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies have shown that sleep disorders in adults have been associated with a large variety of diseases, such as obesity, arterial hypertension, dyslipidemia, and diabetes mellitus (DM) [7][8][9] , as well as increased cardiovascular morbidity/ mortality 10,11 . Nowadays, the harmful effects associated with sleep disorders happen among several age groups, besides the elderly 12 . Recent studies have consistently demonstrated a close relationship between sleep disorder and cardiovascular diseases in different age groups, including adolescents 4,5,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the harmful effects associated with sleep disorders happen among several age groups, besides the elderly 12 . Recent studies have consistently demonstrated a close relationship between sleep disorder and cardiovascular diseases in different age groups, including adolescents 4,5,12 . In clinical practice, intima-media thickness, mainly carotid (CIMT), has been used as a marker of subclinical atherosclerosis 13 .…”
Section: Introductionmentioning
confidence: 99%